Pilot-scale microfluidic solvent extraction of high-value metals. (31st May 2022) - Yang, Daisy; Navvab Kashani, Moein; Priest, Craig
Highlights: A multistream microchip was numbered-up to successfully extract high-value metals. The platform provides a throughput up to 1 L/h. Extraction efficiency was monitored with increasing throughput. The approach to steady state in multistage extraction was monitored by pH and ICP-MS. Abstract: Numbering-up of processing units is essential for industrial-scale microfluidic solvent extraction. In the present work, a multistream microchip was numbered-up to successfully extract high-value metals (including platinum and rare earth elements) from industrial leach solutions. The platform provides orders of magnitude higher throughput (up to 1 L/h) compared with previously reported stream-based microfluidic solvent extraction, without compromising extraction performance. Extraction efficiency was monitored with increasing throughput. The approach to steady state in a three-stage counter-current extraction circuit was monitored by pH and inductively coupled plasma mass spectrometry of the aqueous raffinate. This pilot-scale microfluidic solvent extraction shows potential for refining high-value (technology or precious) metals and as a laboratory tool for rapid screening of reagents and process conditions.